The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1021/jm960011w
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Pyrrolo[2,3-d]pyrimidine and Pyrimido[4,5-b]indole Derivatives:  Structure−Activity Relationships of Potent, Highly Stereoselective A1-Adenosine Receptor Antagonists,

Abstract: A series of 33 novel, mostly chiral pyrrolo[2,3-d]pyrimidine and pyrimido[4,5-b]indole derivatives has been synthesized and investigated in radioligand binding assays at the high-affinity adenosine receptor (AR) subtypes A1 and A2a. The compounds can be envisaged as adenine and hypoxanthine analogs lacking the nitrogen in the 7-position (7-deazaadenines and 7-deazahypoxanthines). 7-Deazaadenines were much more potent than 7-deazahypoxanthines at AR with A1AR affinities in the low-nanomolar range, extraordinari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…this article and the four taken from the literature (R and S ADPEP [Muller et al, 1990] and R and S DPEAP [Muller et al, 1996]) are shown in Table 3. They were selected for the molecular modeling study because the six pairs of enantiomers considered bear the chiral substituent, respectively, at positions corresponding to N 6 and N(9) of the adenine nucleus.…”
Section: The Molecular Structures and The Binding Constant (K I ) Valmentioning
confidence: 99%
See 3 more Smart Citations
“…this article and the four taken from the literature (R and S ADPEP [Muller et al, 1990] and R and S DPEAP [Muller et al, 1996]) are shown in Table 3. They were selected for the molecular modeling study because the six pairs of enantiomers considered bear the chiral substituent, respectively, at positions corresponding to N 6 and N(9) of the adenine nucleus.…”
Section: The Molecular Structures and The Binding Constant (K I ) Valmentioning
confidence: 99%
“…The hypothesis that some antagonists of the A 1 adenosine receptors may arrange themselves in the binding site according to different orientations has been suggested by other groups with regard to xanthine derivatives [Dooley et al, 1992;Dudley et al, 1993]. A more recent article concerning a class of chiral ligands characterized by quite a high molecular diversity also suggests different possibilities of arrangement of these ligands in the binding site [Muller et al, 1996].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This compound had very little selectivity over the A 2A receptor [79]. Later work showed the 4-NH 2 group (i.e., 107) to be favourable, with the inclusion of an aromatic substituent at C(2) and a chiral moiety at N(9) [80].…”
Section: The 6 : 5 : 6-fused Tricyclic Heteroaromatic Systemsmentioning
confidence: 99%